[OP.8A.01] EXERCISE-INDUCED HYPERTENSION AND CARDIAC HYPERTROPHY IN EPINEPHRINE-DEFICIENT MICE. (September 2016) - Mendes, P.; Martinho, R.; Leite, S.; Leite-Moreira, A.; Lourenço, A.; Moreira-Rodrigues, M.
Abstract : Objective: Phenylethanolamine-N-methyltransferase (Pnmt) is required for the conversion of norepinephrine to epinephrine. Bao et al (2007) described that Pnmt-knockout (Pnmt-KO) mice have an increased ratio of left ventricular (LV) posterior wall thickness to internal dimensions (LVPW/LVID) but not overall cardiac hypertrophy. Pnmt-KO mice showed normal resting blood pressure (BP) but became hypertensive during treadmill exercise. The aim of this study was to evaluate cardiac morphological and functional alterations after chronic exercise in Pnmt-KO mice. Design and method: PCR-based genotyping was performed at the Pnmt locus of 10-week-old Pnmt-KO (Pnmt-/-) and WT mice (129x1/SvJ). Epinephrine and norepinephrine were quantified by RP-HPLC-ED in adrenal glands. Animals were submitted to a 6-week exercise training program. BP was measured by a photoelectric pulse detector. Mice were anesthetized (sevoflurane, 8%) and cardiac morphology and function were evaluated by echocardiography followed by morphometric analysis. Results: Epinephrine levels were vestigial in Pnmt-KO compared with WT mice. There were no differences in systolic and diastolic BP between untrained Pnmt-KO and WT mice. However, trained Pnmt-KO mice showed a significant increase in systolic BP when compared to trained WT mice. Our findings also showed that the ratios between heart weight (HW/BW) and LV weight (LVW/BW) and body weight (BW) were significantly increased in trained compared to untrained Pnmt-KO mice. Trained Pnmt-KO mice presented higher HW/BW than trained WT mice. Untrained Pnmt-KO mice display echocardiographic results similar to those reported by Bao et al (2007) while LVPW and IVS thicknesses, LV end-diastolic internal dimension (LVIDd) and LV mass indexed for body surface area (LVMi) were significantly increased in trained Pnmt-KO mice, indicating overall LV hypertrophic changes. Indexed LV end-diastolic volume (LVEDVi), indexed stroke volume (SVi) and cardiac index (CI) were significantly higher in trained Pnmt-KO than untrained Pnmt-KO mice. Conclusions: In conclusion, the increased BP in Pnmt-KO mice in response to exercise appears to be associated with an increase in LV wall thickness and chamber volume suggesting hypertrophic remodelling of the LV in Pnmt-KO mice. Epinephrine appears to be essential for maintaining normal BP, probably through β2-adrenoceptors-induced vessel relaxation, and preventing LV hypertrophy in chronic exercise.